It is feasible to perform laparoscopic pancreaticoduodenectomy for patients with prior abdominal operation - Cai, Yunqiang; Wang, Junfeng; Wang, Xin; Li, Yongbin; Gao, Pan; Peng, Bing (Translational Cancer Research, 2018)
Background: A history of intra-abdominal surgery is a relative contraindication for laparoscopic surgery. The safety and feasibility of laparoscopic pancreaticoduodenectomy (LPD) in patients with previous upper abdominal operation (PUAO) are uncertain. Methods: We performed 282 LPD cases from November 2010 to May 2017. A cohort of 84 patients was matched in terms of age, gender, body mass index, American Society of Anesthesiology, tumor size, tumor location, and histopathologic diagnosis (group 1 consisting of 42 cases with PUAO and group 2 comprising 42 cases without PUAO). Data were collected and analyzed retrospectively in terms of demographic characteristics, intraoperative variables, and postoperative variables. Results: Only one patient in group 1 required to convert to hand-assisted surgery due to massive adhesion. No 30-day mortality was reported in both groups. The mean time for adhesiolysis in group 1 was 16 min, but the total operative time (392±41 vs. 385±33 min, P=0.217) and the estimated blood loss (147±32 vs. 162±43 mL, P=0.142) was comparable between the two groups. No statistical difference was observed between the groups in terms of complications and postoperative hospital stay. Conclusions: LPD can be safely performed in patients with PUAO. PUAO should not be regarded as a contraindication for LPD.